Incompressible flow simulation using SIMPLE method on parallel computer - Manshoor, Bukhari (Penerbit UTHM, 2009)
This paper is concerned with the development of a parallel algorithm on cluster of workstation with Parallel Virtual Machine (PVM) for solving the finite difference Navier-Stokes and energy equations. The numerical procedure is based on SIMPLE (Semi Implicit Method for Pressure Link Equations) developed by Spalding. The governing equations are transformed into finite difference forms using the control volume approach. The hybrid scheme which is a combination of the central difference and up wind scheme was used in obtaining a profile assumption for parameter variations between the grids points. The Domain Decomposition Method (DDM) was used to decompose the domain into a small domain and each of the domains was solved by different processors. The accuracy of the parallelization method was done by comparing with a benchmark solution of a standardized problem related to the two dimensional buoyancy flow in a square enclosure. The results are shown in the forms of contour maps of non-dimensional temperature and velocities.